Poor Community Joint Business Group (KUBE-FM) Kemuning 1 in Nagari Minangkabau, Sungayang sub-District, Tanah Datar District - Rahmadini Winia; Wirdatul Aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research was motivated by the success of Kemuning 1 KUBE-FM which was allegedly due to the coaching approach to the group members provided by the coach of the group. This research aimed to describe the direct coaching approach based on individual and group coaching aspects. In addition, this research is also to describe the indirect coaching approach based on the letter, brochure, and television aspects. This is descriptive qualitative research with a case study approach. The data source of this research consists of the members of Kemuning 1 as the research subjects, and the research informant consists of group coach, social worker companion, and the community in the Kemuning 1 KUBE-FM environment. The data collection techniques are interviews, observation, and documentation. The data analysis techniques are reduction data, data presentation, and drawing conclusions. The data validity technique employs source triangulation. The research result revealed that Kemuning 1 KUBE-FM success based on (1) the Direct coaching approach signifies good results in terms of problems faced by the group members and how they solve the problems. (2) The indirect coaching approach signifies good results in terms of the coaching approach to the group members in which it already supports the business smoothness carried out by group members. It is recommended that the group coach who conducts KUBE-FM would be able to develop a community joint business program, namely, establishing other kinds of joint business, such as KUBE Farming, KUBE home industry.Keywords: KUBE-FM, Coaching Approach